Proposição de indicadores para avaliação de desempenho de redes de cooperação - Adam, Carla Regina (2006)
This study appoaches the issue of the performance evaluation of the horizontal nets supported by The Cooperation Networks Program, in the Rio Grande do Sul State, that has been consolidating as national reference in the incentive for the formation of associative nets. Through a specific methodology, the universities associated to the State act on the support to formation, development and networks consolidation. Despite of having its effectiveness proved, the program methodology doesn t contemplate, so far, systemized tools that evidence the evolution of this type of organization. Based on this evidence, we tried to develop a system that directs the performance evaluation of the cooperation horizontal networks, supported by the Program. The study suggests the performance evaluation be achieved in accordance with structure of nets working, respecting the distribution of the activities developed by the responsible areas. The systematic proposed doesn t contemplate the individual performance evaluation of the enterprises networks participant, as well as it doesn t delimit quantitative levels for the indicatives. To the attendance of the proposed objectives, it was achieved an exploring study, by a bibliographic research, discussions forum with the specialist technicians of the Cooperation Networks Program and the variants identification, called here as performance indicatives. The research procedure was divided into two stages. The first as a qualitative way tried to identify the specialist technician suggestion about the indicatives related to the networks activities, getting the number of 46 indicatives. The second stage, as a quantitative way, was sub-divided into two phases, which we tried to identify the perception of the specialist technicians about the importance and performance of the indicatives. The use validity of these indicatives was verified by the analysis of the convergence of results, organized by rankings. The smaller difference among the positions the better this indicative tends to measure the net performance. We got the convergence in 36 from the 46 indicatives suggested. The study conclusion points to the necessity to split up the researches in this area, whereas the nets inter-organizing formation makes part of strategies of several economies in development. It s good to emphasize this organization way requires instruments that permits the evaluation of its collective performance. It intends the study can be used as a guide to the performance evaluation of the cooperation networks.